Exceptionally High Blocking Temperature of 17 K in a Surface‐Supported Molecular Magnet. Issue 40 (15th August 2021) - Paschke, Fabian; Birk, Tobias; Enenkel, Vivien; Liu, Fupin; Romankov, Vladyslav; Dreiser, Jan; Popov, Alexey A.; Fonin, Mikhail
Abstract: Single‐molecule magnets (SMMs) are among the most promising building blocks for future magnetic data storage or quantum computing applications, owing to magnetic bistability and long magnetic relaxation times. The practical device integration requires realization of 2D surface assemblies of SMMs, where each magnetic unit shows magnetic relaxation being sufficiently slow at application‐relevant temperatures. Using X‐ray absorption spectroscopy and X‐ray magnetic circular dichroism, it is shown that sub‐monolayers of Dy2 @C80 (CH2 Ph) dimetallofullerenes prepared on graphene by electrospray deposition exhibit magnetic behavior fully comparable to that of the bulk. Magnetic hysteresis and relaxation time measurements show that the magnetic moment remains stable for 100 s at 17 K, marking the blocking temperature T B(100), being not only in excellent agreement with that of the bulk sample but also representing by far the highest one detected for a surface‐supported single‐molecule magnet. The reported findings give a boost to the efforts to stabilize and address the spin degree of freedom in molecular magnets aiming at the realization of SMM‐based spintronic units. Abstract : Sub‐monolayers of Dy2 @C80 (CH2 Ph) dimetallofullerene single‐molecule magnets are prepared on a graphene monolayer by electrospray deposition. Magnetic hysteresis and relaxation time measurements show that the magnetic moment remains stable for 100 s at 17 K, marking the blocking temperature T B(100), being not only in excellent agreement with that of the bulk but also representing by far the highest one detected for a surface‐supported single‐molecule magnet.